Ophthalmic Biomaterials - Muirhead, Ben (My University, 2017)
This thesis will explore, both generally and very specifically, the role of biomaterials in drug delivery and tissue engineering applications. A novel therapeutic conjugate to treat dry eye disease using hyaluronic acid and sulfadiazine was created and tested using a benzalkonium chloride induced dry eye model. Thermoresponsive hydrogels based around poly(n-isopropylacrylamide) were synthesized to create a potential in situ gelling cell scaffold for cell delivery to the subretinal space. Finally, a mucoadhesive micelle was developed as a platform delivery system to increase bioavailability of drug in anterior segment therapeutics.
Keywords: Biomaterials; Ophthalmology; cell delivery; cell scaffold; drug delivery; mucoadhesive